Structural diversity of the major surface antigen of Plasmodium falciparum merozoites. - Schwarz, R T (1986)
The structures of the major merozoite surface antigen of Plasmodium falciparum and the gene encoding it were indistinguishable for the Wellcome strain and the Thai clone T9/94 but different for clones T9/96, T9/98, and T9/101. The central portion of the gene is subject to the greatest variation in structure. The protein from all five lines was found to be posttranslationally modified by covalent addition of both carbohydrate and fatty acid.